Perputaran Piutang, Perputaran Modal Kerja, Perputaran Kas dan Struktur Modal terhadap Profitabilitas - Bayu Wulandari; Julyani Julyani; Santi Santi; Jessica Sulastio; Lucianto Hanafie (COSTING : Journal of Economic, Business and Accounting, 2020)
In the midst of an unstable Indonesian economy, it requires every company to be able to face and anticipate all situations to survive in increasingly fierce competition. This research aims to test whether receivables turnover, working capital turnover, cash turnover and capital structures have an influence on profitability in large and small trade sector manufacturing companies listed on the stock Exchange Indonesian. This research is a type of quantitative descriptive research which uses data from 62 companies manufacturing large and small trade sectors listed on the Indonesia Stock Exchange.The sampling method used in this study was purposive sampling and obtained as many as 18 samples. The research methods used are methods of descriptive analysis and analysis methods of multiple linear regression.The results showed that in a partial receivables turnover has no significant effect on profitability,working capital turnover has no negative and significant effect on profitability,cash turnover has no effect Significant impact on profitability and the capital structure has no significant effect on the profitability listed on the Indonesia Stock Exchange.Simultaneously the receivables turnover,working capital turnover,cash turnover and capital structure together have significant effect on the company's profitability measured from the profitability listed on the Indonesia Stock Exchange. Keywords: Receivables Turnover, Working Capital Turnover, Cash Turnover, Capital Structure, and Profitability.